The role of attitude toward nature in learning about environmental issues - Baierl, Tessa-Marie; Kaiser, Florian G.; Bogner, Franz X. (Frontiers in Psychology, 2024)
Attitude toward nature and environmental attitude are two distinct propensities that both further learning about the environment. The present study builds upon prior research by investigating the role of attitude toward nature in learning about environmental issues. In a sample of 1,486 university, middle and high school students (Mage = 15.25, SD = 3.2), we first calibrated a pool of items expressing attitude toward nature. We found differences in how adolescents expressed their appreciation for nature at different ages. It is essential to consider these differences to accurately ascertain adolescents’ attitudes toward nature. We then conducted a mediation test. Whereas attitude toward nature determined the levels of knowledge students gained and retained, environmental attitude fully mediated the environmental knowledge subsequently demonstrated by the students. Our research suggests that researchers and educators may benefit from taking an experiential approach to learning about sustainable development by promoting appreciation for nature.